RELEVANSI HUKUM PIDANA INTERNASIONAL DALAM MENGANALISIS KASUS PERDAGANGAN MANUSIA KHUSUSNYA WANITA dan ANAK-ANAK, SEBAGAI SALAH SATU JENIS KEJAHATAN TRANSNASIONAL - Eva Arief (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
Transnational crime is a crime that crosses state borders, is part of the International crime. Perceived transnational crime continues to increase, so that the international community has agreed on an International treaty "The United Nations Convention Against Transnational Organized Crimes" signed in Palermo, Italy in December 2000. The Convention is complemented by two protocols, namely "Protocol Against the Smuggling of Migrants by Land, Air and Sea "and the" Protocol to Prevent, Suppress and Punish Trafficking in Persons ". Protocol The second is the basis for countries to combat human trafficking, especially women and children, in which this crime is transnational crime is growing faster than most crimes because of international organized crime regarded human beings as a commodity that can generate profit very large.